Produção de etanol de segunda geração e de ácido láctico a partir da casca de arroz e do capim-elefante utilizando pré-tratamento a vapor e hidrólise enzimática - Montipó, Sheila (My University, 2017)
Rice husk (RH) and elephant grass (EG) are abundant lignocellulosic raw materials in the South of Brazil and a feasible resource that can be converted into a range of value-added chemicals and biofuels. In this study, both biomasses were investigated by uncatalyzed steam explosion followed by hydrolysis, in order to obtain a satisfactory content of C6-sugar in the water insoluble solids (WIS) and C5-sugar in the liquor to subsequent fermentation aiming ethanol and lactic acid (LA), respectively. Thus, the effect of the variables temperature (181 to 229 °C for RH and 178 to 212 °C for EG) and residence time (1.6 to 11.4 min for RH and 5.9 to 10.1 min for EG) employed in the pretreatments was evaluated by means of experimental design. Altogether, among the different pretreatments performed, those involving the use of RH favoured the recovery of hemicellulose contained in the liquor, whereas those involving the use of EG were more susceptible to the recovery of cellulose contained in the WIS. In addition, it was possible to verify that intermediate temperature conditions and prolonged periods of time led to the obtaining of balanced contents of glucose in the pretreated material and xylose in the filtrate, in a sole experiment. Further pretreatments with EG, conducted with the aid of an acid catalyst, have shown an improvement in the yield of the sugars of interest in each of the target fractions. For the following hydrolysis and fermentations, the optimized condition of 205 °C for 11.5 min was employed for RH pretreatment; in turn, the condition of 190 °C for 5 min was employed for EG pretreatment, which was impregnated with 2% (w/w) of sulfuric acid. For both pretreated feedstocks, enzymatic hydrolysis assays indicated the advantages in the use of high solids loading, resulting in a more concentrated glucose and promoting the subsequent ethano production. Thus, the WIS was subjected to hydrolysis using high solids consistency arranged with distinct doses of enzymes. Assays employing 20% (w/v) solids loading and an enzyme dosage of 20 FPU g-1 substrate augmented the conversion of cellulose into glucose, releasing 33.68 g L -1(RH) and 95.57 g L-1 (EG). Different fermentation strategies were employed aiming ethanol production: prehydrolysis, separate hydrolysis and fermentations, and simultaneous saccharification and fermentation; the latter of which increased the productivity of the overall process. Ethanol production by accharomyces cerevisiae CAT-1 reached 19.17 g L-1 (RH) and 42.25 g L-1 (EG), after 72 h of cultivation, using WIS as substrate. Filtrates were detoxified and used as a substrate for the production of LA by Lactobacillus buchneri NRRL B-30929. In the specific case of steam-exploded RH, the liquor was previously subjected to hydrolysis with an enzymatic complex produced by Penicillium echinulatum S1M29 strain. Already the pretreatment catalyzed for the EG also acted as an acid hydrolysis. Therefore, the total sugars belonging to each of the liquors were consumed by LA bacteria, and a racemic blend of DL-LA was produced, totaling 12.69 g L-1 (RH) and 13.35 g L-1 (EG), after 30 h of cultivation. The findings of this study suggest that both RH and EG are potential renewable resources which can generate bioproducts from C5-sugars, while producing second generation ethanol from C6-sugars. Likewise, the possible insertion of these raw materials, with low market cost, can foment the generation of processes linked with technological innovation, also contributing to the reduction of environmental problems.
A casca de arroz (CA) e o capim-elefante (CE) são matérias-primas lignocelulósicas abundantes no sul do Brasil, sendo fontes disponíveis para a conversão a inúmeros insumos químicos com valor agregado e biocombustíveis. Neste estudo, ambas as biomassas foram pré-tratadas por explosão a vapor não-catalisada, seguido de hidrólise, com o intuito de obter teores elevados de hexoses nos sólidos insolúveis em água (water insoluble solids – WIS) e pentoses no licor, para posterior fermentação a etanol e ácido láctico (AL), respectivamente. Assim, o efeito das variáveis temperatura (181 a 229 °C para a CA e 178 a 212 °C para o CE) e tempo (1,6 a 11,4 min para a CA e 5,9 a 10,1 min para o CE), utilizadas nos prétratamentos, foram avaliadas através de um delineamento experimental. De modo geral, dentre os distintos pré-tratamentos executados, aqueles envolvendo o uso da CA favoreceram a recuperação da hemicelulose contida no pré-hidrolisado, enquanto que aqueles envolvendo o uso do CE foram mais susceptíveis à recuperação da celulose contida no WIS. Adicionalmente, foi possível verificar que condições intermediárias de temperatura e períodos prolongados de tempo conduziram à obtenção de teores balanceados de glicose no material pré-tratado e de xilose no filtrado, em um único experimento. Pré-tratamentos posteriores com o CE, conduzidos com agente catalisador ácido, evidenciaram uma melhora no rendimento dos açúcares de interesse em cada uma das frações-alvo. Para as hidrólises e fermentações seguintes, a condição otimizada de 205 °C, por 11,5 min, foi usada para o pré-tratamento da CA; por sua vez, 190 °C, por 5 min, foi empregada para o pré-tratamento do CE, usando-se 2% (m/m) de ácido sulfúrico. Para ambos os materiais pré-tratados, ensaios de hidrólise enzimática indicaram as vantagens em empregarem-se cargas de sólidos elevadas, resultando solução mais concentrada em glicose, favorecendo a subsequente produção de etanol. Assim, os WIS foram submetidos à hidrólise usando elevada carga combinada com diferentes doses de enzimas. Ensaios empregando carga de 20% (m/v) de sólidos, aliados a uma dose de enzima de 20 FPU g-1 substrato, beneficiaram a conversão de celulose em glicose, liberando 33,68 g L-1 (CA) e 95,57 g L-1 (CE) de glicose. Estratégias distintas de fermentação foram empregadas visando-se à produção de etanol: pré-hidrólise, hidrólise e fermentação separadas, e, sacarificação e fermentação simultâneas, sendo que esta última incrementou globalmente a produtividade do processo. A produção de etanol por Saccharomyces cerevisiae CAT-1 foi de 19,17 g L-1 (CA) e 42,25 g L-1 (CE) após 72 h de cultivo, empregando-se WIS como substrato. Ainda, os filtrados foram destoxificados e empregados como substrato na produção de AL por Lactobacillus buchneri NRRL B-30929. No caso específico da CA explodida, o licor foi previamente submetido à hidrólise com um complexo enzimático produzido pelo fungo Penicillium echinulatum S1M29. Já o pré-tratamento catalisado para o CE atuou também como uma hidrólise ácida. Logo, os açúcares totais de cada um dos licores foram consumidos pela bactéria ácido-láctica, produzindo-se uma mistura racêmica de DL-AL, totalizando 12,69 g L-1 (CA) e 13,35 g L-1 (CE) após 30 h de cultivo. Os dados resultantes indicam que tanto a CA quanto o CE são potenciais recursos renováveis, que podem gerar bioprodutos da plataforma de building blocks com base em pentoses e, ao mesmo tempo, produzir etanol de segunda geração a partir de hexoses. Ademais, a possível inserção destas matérias-primas, de baixo custo de mercado, pode fomentar a geração de processos com inovação tecnológica, contribuindo, além disso, para a redução de problemas de caráter ambiental.
Keywords: Capim-elefante; Álcool; Ácido lático; Cascas; Arroz; Pennisetum purpurem; Alcohol; Lactic acid; Bark; Rice